Aproximación al hecho religioso en la agenda informativa de la prensa española - Cordero Morales, Fernando (Estudios sobre el Mensaje Periodístico, 2007)
The religious experience is part of the human experience and, as anything that arouses our interest, becomes an objective for mass media. The press has an agenda with mechanisms to approach issues that can become news. The theory of agenda-setting establishes some significant elements that can be applied to the information on religious issues. However, as in many other areas of our lives, there is a certain tension between the journalistic interests, the religious institutions’ agenda and the public opinion status. At the same time, we consider the relevance of the gatekeeper as a channel and agent of creation of the news.